(untitled) (Economics and region, 2019)
The problems of construction enterprises in Ukraine, destructive factors of influence on their financial results are investigated. There is an opinion on the need to improve the system of regulation of construction and construction enterprises and to develop a state strategy for reforming the construction industry on the basis of innovations, energy efficiency, environmental safety and social orientation of the development of the national economy of Ukraine. In order to solve the problems of construction companies, the elimination of destructive factors impact on their financial situation should develop a national strategy to reform the construction industry based on innovation, energy efficiency, environmental safety and social orientation of the national economy of Ukraine. Common scientific methods of statistical research, analysis, generalization are used.